DiAlert: a lifestyle education programme aimed at people with a positive family history of type 2 diabetes and overweight, study protocol of a randomised controlled trial - de Wit Maartje; Verhoeff Arnoud P; Twisk Jos WR; Middelkoop Barend JC; Stronks Karien; Nierkens Vera; Heideman Wieke H; Snoek Frank J (BMC, 2011)
Abstract Background Family history is a known risk factor for type 2 diabetes (T2DM), and more so in the presence of overweight. This study aims to develop and evaluate the effectiveness of a new lifestyle education programme 'DiAlert' targeted at 1st degree relatives of people with T2DM and overweight. In view of the high risk for diabetes and cardiovascular disease in immigrants from Turkish origin living in Western Europe, a culturally appropriate Turkish version of DiAlert will be developed and tested. Methods/design In this RCT, 268 (134 Dutch and 134 Turkish) overweight 1st degree relatives of patients with T2DM will be allocated to either the intervention or control group (leaflet). The intervention DiAlert aims to promote intrinsic motivation to change lifestyle, and sustain achieved behaviour changes during follow-up. Primary outcome is weight loss. Secondary outcomes include biological, behavioural and psychological indices, along with process indicators. Measurements will take place at baseline and after 3 and 9 months. Changes in outcomes are tested between intervention and control group at 3 months; effects over time are tested within and between both ethnic groups at 3 and 9 months. Discussion The DiAlert intervention is expected to be more effective than the control condition in achieving significant weight loss at 3 months, in both Dutch and Turkish Dutch participants. Trial registration Netherlands National Trial Register (NTR): NTR2036